PERSEPSI TERHADAP KEPEMIMPINAN TRANSFORMASIONAL SEBAGAI PEMODERASI PENGARUH ANTARA KESEIMBANGAN KERJA HIDUP PADA KOMITMEN ORGANISASIONAL KARYAWAN - Azliyanti, Elfitra (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2017)
This research has two objectives. First, to examine the effect of work life balance onorganizational commitment. Second, the moderating of perception of transformational leadershipon work life balance the influence to organizational commitment perceived organizational supporton emotional intelligence to job performance. The subject of the research is employes who work in2 hospitals in Yogyakarta. The data is collected by using questionnaires, distributed to 200employees. The survey was conducted on 200 nurses Hospital in Jogjakarta. Total of 175questionnaires that were collected questionnaires, only 165 questionnaires that can be processed.Data analysis using moderated regression analysis. The results showed that the balance of lifesignificantly negative effect on affective and normative commitment to employees, but had no effecton employee continuance commitment. Perceptions of transformational leadership is not amoderator effect of work life balance relations on organizational commitment of employees.Key words: work life balance, affective commitment, continuance commitment, normativecommitment, the perception of transformational leadership and moderation